The nexus between human development, official development assistance, carbon emissions, and governance in developing countries for the realization of sustainable development goals - Jean Tony Ezako (Cogent Economics & Finance, 2024)
The paper aims to analyze human development through its interactions with environ- mental protection, governance, and official development assistance (ODA) in develop- ing countries. This is done to allow the decision-makers of the latter to have an optimal approach to sustainable development goals (SDGs). For this matter, we used data from 56 developing countries for the period from 2005 to 2019 with the novel cross-sectionally augmented ARDL and augmented mean group (AMG). Interactive terms have been used for robustness checks. The results showed that, for low-income countries, ODA harms human development while governance effectiveness has a posi- tive impact. The combination of governance effectiveness and ODA has a positive impact on human development. The same positive impact is found for the combin- ation of governance and carbon emissions on human development. For middle- income countries, the findings showed that carbon emissions have a positive impact on human development. The combination of carbon emissions and ODA has a posi- tive impact on human development. We recommend that; first, low-income countries' policymakers focus on the achievement of the combination of SDG 16 and SDG 17 with SDG 16 as the central piece for SDGs realization; Second, middle-income coun- tries' policymakers focus on the achievement of the combination of SDG 8, SDG 16, and SDG 17 with SDG 8 as the central piece for SDGs realization. ODA donors must consider the needs of the countries receiving assistance and ease the conditions for obtaining aid. Moreover, we recommend collaboration focused on technology transfer between developed and developing countries.
Keywords: C21; I3; O2; Q5; 330; Human development; environmental protection; cross-section ARDL; development assistance:energy consumption